Gaussian process model based multi-source labeled data transfer learning for reducing cost of modeling target chemical processes with unlabeled data. (December 2021) - Chan, Lester Lik Teck; Chen, Junghui
Abstract: In chemical industries, many important tasks such as process design and monitoring rely on the availability of a good model. A high-performance data-driven prediction model is desired and requires labeled data. However, this can result in increased expenses in modeling because of the effort required to obtain the labeled data. The transfer learning (TL) approach has been considered to reduce the cost of acquiring labeled data but the case of unlabeled data in transfer learning for chemical process modeling has not been considered. A new Gaussian process (GP) model-based TL under the setting with unlabeled data is proposed in this work. By leveraging the predictive variance, the transfer of knowledge aims to increase the level of confidence in the prediction after transfer. The main contributions of the article include proposing a new transfer learning method under the setting with unlabeled data based on GP model, as well as the inclusion of threshold in the weighting of transfer. The use of GP model allows a statistical component to be taken into account in the transfer learning objective function whereas the threshold in the weighting of transfer acts as a mechanism that reject unwanted information is considered. The threshold thus provides a parameter in the consideration of the effectiveness of the transfer. The proposed method is demonstrated using a case study and its applicability to an industrial melt-index data is also shown. Highlights: Transfer learning for chemical processes with unlabeled data. Gaussian process model based framework facilitate regularizer in formulation. Weighting threshold provide a degree of robustness to the transfer of information. Application to melt index data to demonstrate applicability in industrial setting.